2019
DOI: 10.7759/cureus.4898
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Atorvastatin and Rosuvastatin in Reduction of Inflammatory Biomarkers in Patients with Acute Coronary Syndrome

Abstract: Introduction High-sensitivity C-reactive protein (hs-CRP) has emerged to be a very useful and reliable clinical marker of primary as well as secondary cardiovascular morbidity and mortality. Elevated hs-CRP contributes to underlying atherogenesis and worsens disease prognosis. Along with their lipid-lowering properties, statins also contribute to the alleviation of micro-inflammation and reduces pro-inflammatory markers. The aim of this study is to compare the effects of rosuvastatin and atorvastati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 18 publications
0
8
0
1
Order By: Relevance
“…This may be because our research period is too short. In other studies, the effect of decreasing hs-CRP of the statins was evident after 4 weeks, 6 weeks, and 12 weeks of treatment 15,25 .…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…This may be because our research period is too short. In other studies, the effect of decreasing hs-CRP of the statins was evident after 4 weeks, 6 weeks, and 12 weeks of treatment 15,25 .…”
Section: Discussionmentioning
confidence: 69%
“…In recent years, several studies have been done to compare the effects of high-intensity statins in patients after ACS around the world. Rosuvastatin seems to be more effective than atorvastatin in reducing LDL-c and hs-CRP levels 15,16 . However, very few clinical trials have been conducted in Vietnam to discuss this issue.…”
Section: Introductionmentioning
confidence: 98%
“…A study like ours also revealed similar results with the use of atorvastatin and rosuvastatin in ACS. Kumar et al concluded better results with the use of rosuvastatin by significantly reducing the hsCRP and ESR [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…High-dose statins can accelerate the decrease in hsCRP levels after ACS [ 4 ]. In an open-label randomized trial study of the comparison of atorvastatin and rosuvastatin, it was found that both groups showed statistically significant reduction in serum hsCRP levels (p<0.0001), but rosuvastatin had a more effective role in reducing micro-inflammation in ACS patients [ 5 ]. Furthermore, in a study by Calahorra et al, recurrent atherosclerotic cardiovascular disease (ASCVD) event rates were 2.73 (95% CI: 1.63, 4.25) cases/100 person-years and 2.34 (95% CI: 1.17, 4.10) cases/100 person-years in the atorvastatin and rosuvastatin groups, respectively, which may also be related to reduction in inflammatory markers after first cardiovascular event [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…31 No contexto clínico, a atorvastatina reduz processos ateroscleróticos 32 e quadros clínicos de síndrome coronária aguda. 33 De fato, dentre os diversos efeitos pleiotrópicos da atorvastatina, é robusta a sua capacidade vasoprotetora. Ainda assim, não há evidências suficientes que atestam sobre os efeitos e os possíveis mecanismos envolvidos nas ações da atorvastatina, sob a perspectiva do músculo liso vascular e, de forma inédita, sob o PVAT como tecidos inflamatórios em condições de SM.…”
Section: Introductionunclassified